Strategies Used By The High And Low Writing Ability Students To Develop Writing Skill At Muhammadiyah University Of Surakarta - Qomariyah, Siti Lailatul; , Mauly Halwat Hikmat, Ph. D; , Aryati Prasetyarini, M.Pd (2014)
The research paper aims at finding out and describes strategies used by the high and low writing ability students in developing writing skill at Muhammadiyah University of Surakarta. The type of this research is case study. The subjects of this research are four students chosen based on the score of writing subject. The methods of collecting data are interview and observation. The result of this research shows that two students who have high mark and two students who have low mark in writing subject use almost all learning strategies proposed by O'Malley and Chamot. However their attention in learning is different. Strategies used by the high writing ability students are twelve strategies which consist of five metacognitive strategies: advance organizer, directive attention, selective attention, self management and self evaluation; five cognitive strategies: resourcing, note taking, translation, summarizing, repetition, and two social affective strategy: namely question for clarification and cooperation. Strategies used by the low writing ability students are six strategies which consist of three metacognitive strategies: directive attention, self management, self- evaluation, one cognitive strategy that is translation, and two social affective strategies; question for clarification and cooperation. Of the four students, the students who have high mark in writing subject uses highest number of learning strategies proposed by O'Malley and Chamot. They use more metacognitive strategies than cognitive and social-affective strategies.